Validation of the Chinese Version of the Questionnaire for Impulsive-Compulsive Disorders in Parkinson's Disease - Xu, Tian; Cao, Lanxiao; Long, Wenying; Zhao, Guohua (Frontiers in Neurology, 2021)
Background: Impulse control and related disorders (ICRDs) have gained recognition as a serious complication of Parkinson's disease (PD) and are related to poor quality of life and devastating financial and social problems. This study aimed to evaluate the usefulness of the Questionnaire for Impulsive-Compulsive Disorders in Parkinson's Disease (QUIP) and to estimate the risk factors for ICRDs in Chinese patients with PD. Methods: The Chinese version of QUIP (C-QUIP) was used to assess motor and non-motor signs and symptoms of PD in 207 patients. ICRDs were diagnosed via interviews of patients or their caregivers, and the clinical characteristics of patients with and without ICRDs were compared. Results: The sensitivity, specificity, positive predictive value, negative predictive value and accuracy of the C-QUIP were 100%, 84.56%, 39.47%, 100% 85.98%. The prevalence of each disorder among participants diagnosed via interview was pathological gambling (0%), hyper-sexuality (1.83%), compulsive shopping (0.61%), binge eating (4.27%), hobbyism (1.83%), punding (0.61%), walkabout (0.61%), and dopamine dysregulation syndrome (3.66%). PD patients with ICRDs had longer PD duration, higher Hoehn and Yahr stage, Non-Motor Symptoms Scale (NMSS), and Hamilton-Depression Rating Scale (HAM-D), and also received a larger mean levodopa equivalent dose (LED), dosage of levodopa and dopamine agonist only LED (DA-LED) than did PD patients without ICRDs. Conclusions: Given its psychometric properties, the C-QUIP is a valid and rapid screening instrument for the assessment of ICRDs in patients with PD. Higher Hoehn and Yahr staging, and NMSS and HAM-D scores, and a larger mean LED and levodopa dosage are risk factors for ICRDs.